Kepuasan Kerja Karyawan Pada UMKM : Perspektif Manajemen Rantai Pasok - Latuconsina, Zainuddin; Matdoan, Arsad; Laitupa, Azis; Yusuf T, Glen Andre; Tutupoho, Saleh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study is to look at how elements of supply chain management, such as information sharing, management leadership, customer engagement, and supplier engagement, impact employee job satisfaction in micro, small, and medium enterprises (MSMEs) in Ambon City. Data was collected through questionnaires that were distributed to owners, managers, and employees of MSMEs in the culinary and handicraft sectors. Quantitative approaches and the Partial Least Square (PLS) method were used to collect data. The results of the analysis show that management leadership and customer engagement have a positive and significant effect on employee job satisfaction. In contrast, sharing information, while having a positive effect, does not have a significant impact; Supplier involvement has a negative and insignificant effect. The results show that to improve job satisfaction, internal communication and supply chain integration must be improved, as well as more participatory leadership and more responsive relationships with customers. In an effort to improve employee welfare and the competitiveness of MSMEs in Ambon, this study provides practical implications for MSME managers and other stakeholders